(untitled) (International Journal of Physiotherapy, 2025)
Background: Adhesive capsulitis, commonly known as frozen shoulder, is a debilitating condition in which the pain and stiffness progressively worsen, restricting the motion of the shoulder joint, with functional limitation. Advanced technologies, such as Xsens Gait Motion Analysis , can be used for real-time 3D motion capture, making them very helpful for the precise assessment and management of musculoskeletal disorders. Case summary: A 43-year-old male with a two-month history of localized pain in the anterior and lateral aspects of the right shoulder reported difficulty with overhead activities and functional tasks. He had decreased active and passive ranges of motion in shoulder flexion and abduction. The initial clinical examination indicated adhesive capsulitis. Detailed kinematic data with specific movement deficits were identified by using Xsens inertial sensors. Based on the study, a structured physiotherapy program was designed, encompassing manual therapy, stretching exercises, and progressive strengthening exercises. Progress was monitored through regular follow-ups, and interventions were adjusted as needed. Outcome measures: NPRS – Numerical Pain Rating Scale, SPADI- Shoulder pain and disability index, DASH - Disability of Arm, Shoulder, and Hand Questionnaire are the outcome measures used. Conclusion: Following a 6-week intervention, there was a significant improvement in pain reduction, accompanied by an increase in shoulder range of motion (ROM) and functional capacity in the patient. Motion analysis using Xsens demonstrated a measurable improvement, with a 50% increase in shoulder flexion and abduction, enabling the patient to resume their daily activities. This case demonstrates the value of Xsens inertial sensor technology in enhancing diagnostic precision and guiding proper treatment strategies for adhesive capsulitis, a step toward improved patient outcomes in musculoskeletal rehabilitation.